Análise morfofuncional da espermatogênese do cavalo da raça crioula - Figueiró, Giuliano Moraes (2010)
The goal of this experiment was to describe the testicular biometry, the morphology of seminiferous tubules, determine the intrinsic income of spermatogenesis, and estimate the daily sperm production and the support capacity of Sertoli cells of Crioulo horses out of the breeding season. Ten stallions with a mean age of 48 months were used in this study. The mean body weight of the stallions was of 377.5 kg. The mean testicular weight was of 162.9 grams, the gonadosomatic index was 0.087% and the tubulosomatic index was 0.067%. The proportion of seminiferous tubuli and of intertubular tissue was of 77.97% and 22.03%, respectively. The tubular diameter was of 205μm and the seminiferous epithelium height was of 70μm. The length of the seminiferous tubuli per gram of testicle was of 26.09 meters. The spermatogonial mitosis efficiency coefficient was estimated in 3.9 preleptotene/leptotene spermatocytes produced from each type A spermatogonia. The meiotic index was of 3.9 cells, and the estimated value of cell loss during prophase in meiosis was of 10%. The overall rate of spermatogenesis was of 13.9 cells. The estimated number of Sertoli cells per gram of testis was of 54.8 million, and each Sertoli cell had the capacity to support 9.0 germ cells. The total sperm reserve was an estimated 46.8 billion, and the daily sperm production was of 3.8 billion sperm per testicle, which is equivalent to 23.5 million of sperm per gram of testicle. It was concluded that the data found in this study were similar to other horse breeds. However, the number of Sertoli cells per gram of testicle, the total and per gram daily sperm production was higher to those published in other breeds of horses, which indicate a possible superiority of potential fertility of the Crioulo breed.